4C Skills in Implementing the Project Based Learning Model - Safitri, Erlita Widyadhana; Hendracipta, Nana; Syachruroji, A (CV. Rayyan Dwi Bharata, 2025)
In 21st century education, knowledge alone is not enough for students. 21st Century education requires students to be able to master their own skills. Mastery of the skills in question include Critical Thinking, Creativity, Collaboration and Communication. Efforts to maintain optimal mastery of these skills require interactive classes. In this way, educators are expected to be able to create learning innovations that can be applied by students actively. Therefore, this research was conducted with the aim of describing the 4C skills in implementing the project based learning model for students at SDN Pulogebang 01. The research applied was descriptive with a qualitative approach. The results of the research show that learning planning using the PjBL model has been prepared optimally by educators with the plans made by educators having adjusted to the steps of the PjBL model and taking into account the needs of students. Regarding the implementation of the PjBL model, educators have implemented learning that contains the six stages of project-based learning. Then the learning outcomes regarding students' 4C skills in implementing the PjBL model have gone as expected. It can be seen that in the three class V groups there are several students who are able to think critically, think creatively, and communicate well so they can work together in their study groups.